Colour shifts: On methodologies in research on the polychromy of Greek and Roman sculpture - Østergaard, Jan Stubbe (Proceedings of the Danish Institute at Athens, 2017)
The article offers a partial overview of methodologies of research on the polychromy of Greek and Roman sculpture. The character of the evidence requires an interdisciplinary approach. This evidence is briefly presented, after which aspects of the actual investigation are dealt with, the section on analytical methods dealing only cursorily with invasive techniques. Attention is drawn to the importance of research based experimental reconstruction of polychrome sculptures. Finally, some interdisciplinary research scenarios are described. The article is based on work done within the framework of the ‘Tracking Colour’ project of the Ny Carlsberg Glyptotek and the Copenhagen Polychromy Network, 2009 – 2013, with the support of the Carlsberg Foundation.